(untitled) (Jurnal Hutan dan Masyarakat, 2021)
Local wisdom has a positive influence on the conservation of customary forest. The society should understand the positive impact of the existence of customary forest. Nenek Limo Hiang Tinggi and Nenek Empat Betung Kuning Customary Forest is located in Kerinci Regency. This study aims to determine local wisdom in the conservation efforts of Nenek Limo Hiang Tinggi and Nenek Empat Betung Kuning Customary Forest. Data and information were obtained from the results of field observation and interview with some informants; Depati Ninik Mamak (Customary Functionary), village government and the society. This research used a qualitative approach. The results of this study showed that local wisdom in the conservation of the Nenek Limo Hiang Tinggi and Nenek Empat Betung Kuning Customary Forest has been carried out well in the form of customary rules. Violation of customary rules are divided into three levels (minor, moderate and severe). This study provided an overview that the society’s local wisdom as the efforts to conserve customary forests was done independently by themselves as the society of Nenek Limo Hiang Tinggi and Nenek Empat Betung Kuning.